Introducing Susan Stebbing as a Forerunner of Informal Logic - Gunawardane, Maheshi (Informal Logic, 2025)
Susan Stebbing (1885–1943), Great Britain’s first female professor of philosophy, was an educator, a logician, and a pioneer of public philosophy with a fondness for argumentation and evidential reasoning. Stebbing, whose revival has only recently begun, proposed an original theory of critical thinking and informal logic in the 1930s, which has not yet been taken account of in the history of the field. My paper aims to recognise Stebbing as a forerunner of informal logic during the period of 1930 to 1960. What makes Stebbing an exemplar in the field is her work on critical thinking, detecting logical fallacies, and evaluating arguments.